2022
DOI: 10.3389/fpsyg.2022.819884
|View full text |Cite
|
Sign up to set email alerts
|

Catering to Inclusion and Diversity With Universal Design for Learning in Asynchronous Online Education: A Self-Determination Theory Perspective

Abstract: The Universal Design for Learning (UDL) guidelines were extensively studied to understand inclusive learning and teaching in higher education. However, to date, there have been few studies that approached UDL-based asynchronous university courses from the needs satisfaction perspective in self-determination theory (SDT). To address this gap, researchers designed and implemented two 15-week asynchronous online courses based on UDL. They then tested their effectiveness with college freshmen (N = 225) by adopting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…The UDL principles relate to the culturally responsive pedagogies of multiple pathways to success and student agency of choice. Ismailov and Chiu (2022) examined UDL strategies in online courses and found that the framework supported autonomy and competence but failed to satisfy all learners' needs. Morong and Desbiens (2016) conducted a literature review and proposed guidelines for culturally responsive pedagogies in online learning.…”
Section: Framework For Inclusion and Equitymentioning
confidence: 99%
“…The UDL principles relate to the culturally responsive pedagogies of multiple pathways to success and student agency of choice. Ismailov and Chiu (2022) examined UDL strategies in online courses and found that the framework supported autonomy and competence but failed to satisfy all learners' needs. Morong and Desbiens (2016) conducted a literature review and proposed guidelines for culturally responsive pedagogies in online learning.…”
Section: Framework For Inclusion and Equitymentioning
confidence: 99%
“…According to Hockings [11], "inclusive learning and teaching in higher education refers to the ways in which pedagogy, curricula and assessment are designed to engage students in learning that is meaningful, relevant, accessible to all" (p. 1). Studies over the past decade have provided important information on inclusive learning in higher education at the course level [4,12]. Researchers have highlighted that inclusive learning in higher education requires further investigation of how students are supported [11,13].…”
Section: Literature Review 21 Support For Inclusive Online Learning I...mentioning
confidence: 99%
“…Students need to feel connected and supported in online learning. To facilitate inclusive online higher education, it is crucial to provide support for addressing these three needs of SDT [12]-autonomy, competence, and relatedness. In other words, the support for meeting these three needs should enable accessibility, relevance, meaningfulness, and engagement in online learning environments.…”
Section: Self-determination Theory As a Lens To Study Online Learning...mentioning
confidence: 99%
See 2 more Smart Citations